1999
DOI: 10.1088/0953-2048/12/11/356
|View full text |Cite
|
Sign up to set email alerts
|

SNS and SIS Josephson junctions with dimensions down to the submicron region prepared by a unified technology

Abstract: Several applications of Josephson junctions (JJs) in low-temperature superconducting circuits such as programmable voltage standards and SFQ logical circuits or SQUID sensors require JJs with sub-µm dimensions. A method for preparing superconductor-isolator-superconductor (SIS) JJs as well as superconductor-normal metal-superconductor (SNS) JJs was developed which allows the preparation of both types of junctions by nearly the same technological process. Titanium is used as the normal metal for the SNS JJ. Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The latter feature is in contrast to other conventional overdamped junctions, like Dayem bridges (see, e.g., Ref. [19]), small superconductor-insulator-superconductor (SIS) [20] or intrinsically shunted SNIS JJs [21], which typically have V c of the order of 100 μV. However, SNS junctions combine a number of crucial advantages, making them suitable for the realization of nano-SQUIDs.…”
Section: Introductionmentioning
confidence: 97%
“…The latter feature is in contrast to other conventional overdamped junctions, like Dayem bridges (see, e.g., Ref. [19]), small superconductor-insulator-superconductor (SIS) [20] or intrinsically shunted SNIS JJs [21], which typically have V c of the order of 100 μV. However, SNS junctions combine a number of crucial advantages, making them suitable for the realization of nano-SQUIDs.…”
Section: Introductionmentioning
confidence: 97%
“…This value is substantially larger than other devices fabricated using niobium-normal metal-niobium junctions, usually having I c R n products in the range of hundreds of microvolts up to a few millivolts. 43,44 This can be partially explained by two distinct factors present in our system. First, the short normal metal channel length of 50 nm leads to an inherently high I c (I c ∝ L -1 ).…”
mentioning
confidence: 94%
“…While a precise and reproducible definition of the JJ size is routinely performed with the help of electron-beam lithography, the application of anodic oxidation in such processes remains a challenge. This is due to the fact that the Nb 2 O 5 layer formed during the anodic oxidation creeps under the resist mask protecting the top electrode of the JJ (this is known as 'encroachment' [1,2]). Even for a plasma hardened resist and an anodization voltage of 20 V, a significant encroachment was still observed [1].…”
Section: Introductionmentioning
confidence: 99%
“…Since we found that a certain Nb 2 O 5 thickness is needed to ensure low subgap leakage currents, this was not an option for us. Other groups have replaced the resist mask with an insulating hard mask such as SiO or SiO 2 [2,[7][8][9][10], which entirely eliminates the encroachment. These hard masks have to be removed by an additional process step, either by reactive ion etching (RIE) through the insulator right above the JJ or by chemical mechanical polishing (CMP).…”
Section: Introductionmentioning
confidence: 99%